The effects of organizational culture on employee performance among public servants at a Kelantan state government office / Noorazzila Shamsuddin... [et al.] - Shamsuddin, Noorazzila; Anual, Norazlan; Mohd Firdaus Kozako, Intan Nurul’ain; Ibrahim, Siti Noor Shahiiroh; Abdul Karim, Zatul Himmah (Universiti Teknologi Mara Cawangan Kelantan, 2020)
Employee performance is considered as a measure of human capital quality in an organization. It could either impact the organization negatively or positively. When employees start performing poorly, it worries the management as it affects the entire operation. Meanwhile, several studies in western countries have examined the relationship between organizational culture and employee performance, mentioning that the key to good performance is a strong culture. In a way, having a good organizational culture is like having a strong immune system. The purpose of this study was to determine the relationship between organizational culture and employee performance. Quantitative data were collected using a self-administered questionnaire. A total of 140 employees were identified from the Pejabat Tanah dan Jajahan Kota Bahru, Kelantan Darul Naim (PTJKB). Later, a stratified random sampling technique was applied, and 103 respondents were determined. The questionnaires were distributed randomly to these respondents from eight departments. The findings indicated that a higher level of organizational culture is associated with a high level of employee performance. It was concluded that, based on the beta value, both Involvement Culture and Adaptability Culture had significant influences on employee performance. This study suggested that PTJKB should consider implementing many initiatives to ensure that new employees have a good understanding of their cultures to maintain a supportive work environment that will subsequently improve and promote positive work results